FROM CLASSROOM TO CLINIC: AN ANALYSIS OF ENGLISH FOR NURSING CURRICULUM IN INDONESIA - Kailani, Ahmad; Emi Emilia; Gin Gin Gustine; Rojab Siti Rodliyah (English Review: Journal of English Education, 2025)
Effective communication in healthcare requires nursing professionals to possess strong language proficiency. However, English for Nursing curricula often lack alignment with real-world linguistic demands. This study analyzes an English for Nursing curriculum at a private institution in Indonesia, examining its ideological foundation, curricular model, and alignment with language proficiency requirements. Using content analysis, the research evaluated course syllabi, learning modules, and institutional curriculum guides through the lens of Tyler’s (1949) curriculum rationale and Richards’s (2001) language curriculum ideologies. Findings revealed that while the curriculum emphasized social-economic efficiency, academic rationalism, and professional competency, gaps remained in integrating English proficiency with clinical communication skills. The study highlighted limitations in curriculum design, including inadequate exposure to authentic professional discourse and a misalignment between learning activities and workplace communication needs. These insights inform curriculum development strategies, emphasizing the need for industry-aligned instructional practices and policy reforms. The findings contribute to nursing education discourse in Indonesia and globally, advocating for curricula that better prepare students for professional communication in clinical settings.